2017
DOI: 10.24188/recia.v9.n2.2017.611
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia de papilomatosis en bovinos (Bos taurus) del departamento de Córdoba, Colombia

Abstract: The objective of the present study was determining the frequency of cutaneous pailomatosis occurring in cattle (Bos taurus) in the Department of Córdoba. Of the dermathologyc cases treated in this period (1184), 117 (9.9%) were clinical cases of cutaneous papillomatosis in cattle of different cattle farms of the Department. 42.7% (50/117) were males and 57.3% (67/117) were females. The most affected age group was 12 to 24 months with the highest number of cases (74/117 (63.2%)), followed by those younger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
0
1
1
Order By: Relevance
“…Most of the papillomas were found in the cow`s udders (31.3%), which contrasts with other studies, where they found the lesions mainly in the neck and head (ranging from 19.6-41.7%) or in the rest of the body (59.0%), not specifying, however, papillomas in udder (Violet et al, 2017;Cardona-Álvarez et al, 2018). Once again, it is hypothesized that the differences in results may be due to differences in the group analyzed, which in this investigation were mainly cows from specialized dairy herds, while in the studies in Colombia the productive use of cattle was not mentioned (Violet et al, 2017;Cardona-Álvarez et al, 2018).…”
Section: Resultscontrasting
confidence: 90%
“…Most of the papillomas were found in the cow`s udders (31.3%), which contrasts with other studies, where they found the lesions mainly in the neck and head (ranging from 19.6-41.7%) or in the rest of the body (59.0%), not specifying, however, papillomas in udder (Violet et al, 2017;Cardona-Álvarez et al, 2018). Once again, it is hypothesized that the differences in results may be due to differences in the group analyzed, which in this investigation were mainly cows from specialized dairy herds, while in the studies in Colombia the productive use of cattle was not mentioned (Violet et al, 2017;Cardona-Álvarez et al, 2018).…”
Section: Resultscontrasting
confidence: 90%
“…En este trabajo se incluyeron muestras colectadas de bovinos de las regiones centro y huasteca del estado de San Luis Potosí, México, las cuales poseen climas muy diferentes entre sí (seco árido en el centro y subtropical en la huasteca). A pesar de que la mayoría de las muestras provenían de la región centro, los habitantes de las localidades de la región huasteca del estado informan de forma empírica una mayor incidencia de lesiones sugerentes de infección por PVB lo que concuerda con lo informado por Violet et al (27) quienes señalan una probable asociación entre la frecuencia de presentación de papilomatosis cutánea y climas de tipo tropical lluvioso.…”
Section: Introductionunclassified